The opioid control of LH and FSH release: effects of a met-enkephalin analogue and naloxone. - Grossman, A; Moult, P; Gaillard, R; Delitala, G; Toff, W; Rees, L; Besser, G (1981)
The effect of long-acting analogue of met-enkephalin (DAMME) and naloxone on gonadotrophin secretion has been investigated in man. In menopausal women DAMME induced a progressive fall in LH to approximately 60% of basal levels at 3 h, which was blocked by naloxone; there was a smaller fall in FSH that did not attain statistical significance. However, the LHRH-induced rise in LH and FSH in young male volunteers was unaffected by pretreatment with a high-dose DAMME infusion. Naloxone infusion in young male and female normal subjects produced a significant rise in both LH and FSH. Long-term infusion of naloxone appeared to increase the rate, and possibly the amplitude, of LH pulsatility. These results suggest that met-enkephalin-like opioid peptides exert a tonic inhibitory control of LH release in both menopausal and young subjects of both sexes. This control is most likely to be at the level of the hypothalamus, and involves modulation of pulsatile LHRH release.